Lavinia-Iunia Vasiu, Cristina Bocoș, „O gramatică... altfel. Dezvoltarea competenței gramaticale în limba română ca limbă străină (RLS). Nivelul A2”, Presa Universitară Clujeană, 2023, 240 p. - BĂILĂ, Adelina-Patricia (Studia Universitatis Babeș-Bolyai Philologia, 2025)
The publication of Lavinia Vasiu and Cristina Bocoș is an original book in the field of Romanian as a foreign language (RFL) / Romanian as a second language (RSL): on one hand, because, as the title says, it is Grammar... in a new way, which doesn’t include grammar lessons with theoretical descriptions of grammar content, alongside the classic structural exercises. Instead, it involves acquiring grammar skills through vocabulary and grammar exercises, through written reception activities, through oral and written interaction, through intercultural and mediation activities. On the other hand, because at the basis of developing all exercises and activities lies on authentic style and the motivation of the students. The book tackles one of the most difficult aspects of grammar in Romanian language (both for non-native speakers in their learning process, as well as for teachers of RFL / RSL in their teaching process), such as the subjunctive mood, the personal pronouns in the accusative case, the nouns and the adjectives in the genitive case etc., specific to language level A2.